2017
DOI: 10.29252/ijrm.15.10.3
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of, and risk factors for, mycoplasma genitalium infection among infertile women in Ibadan: A cross-sectional study

Abstract: Background: The association of mycoplasma genitalium (M. genitalium) with infertility has been documented. The infections are asymptomatic and difficult to diagnose. Understanding the associated risk factors will help in facilitating better screening measures for at-risk groups. Objective: The aim was to determine the prevalence of, and risk factors for, M. genitalium infection among infertile women in Ibadan. Materials and Methods: In this cross-sectional study, 402 women (267 infertile and 135 fertile) refer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Of the 22 women with M. hominis infection, 14 (63.6%, Table 1) had low socioeconomic status. Like other STDs, mycoplasma infection is also more common among women of lower socioeconomic strata [29]. However, we must also consider the fact that most of the participants (56/110, 51%) were in the low socioeconomic group and there was not much difference in the prevalence of M. hominis among the different socioeconomic groups (Table 1).…”
Section: Socioeconomic Groupsmentioning
confidence: 99%
“…Of the 22 women with M. hominis infection, 14 (63.6%, Table 1) had low socioeconomic status. Like other STDs, mycoplasma infection is also more common among women of lower socioeconomic strata [29]. However, we must also consider the fact that most of the participants (56/110, 51%) were in the low socioeconomic group and there was not much difference in the prevalence of M. hominis among the different socioeconomic groups (Table 1).…”
Section: Socioeconomic Groupsmentioning
confidence: 99%
“…The differential counts namely monocytes, neutrophils and lymphocytes increased to a large extent as observed in this study, this support the findings of Ginling et al, [27] in green back flounder (Rhombosulea tapirina) exposed to fresh water. The increased observed may be due to release of more of the white cells to combat the stressor [28] .…”
Section: Discussionmentioning
confidence: 99%
“…In vitro and animal experiments have shown that M. genitalium infection can cause tubal cilia swelling, shedding ( Baczynska et al, 2007 ), and hydrosalpinx ( McGowin et al, 2010 ). Another study reported 16.1 and 2.2% positivity for M. genitalium in cervical swabs from infertile and normal women, respectively ( Ajani et al, 2017 ). This is in agreement with the results of a Polish study on M. genitalium (19.9 and 4.4%, respectively; Grzesko et al, 2009 ), which found that the detection rate of M. genitalium in abdominal fluid samples collected by laparoscopy was 5.88 and 0% in infertile and control women, respectively ( Grzesko et al, 2009 ), similar to the results of an Indian study (6.1 and 0.6%; Rekha et al, 2019 ).…”
Section: Mycoplasma Genitalium and The Female Reproductive S...mentioning
confidence: 99%